Calculation of Filter Lifetime Using Empirical Model Applied to Hydrodynamic Column for Phosphate Removal from Greywater - Hairul Khamidun, Mohd; Fazara Md Ali, Umi; Abdullah, Shakila (International Journal of Engineering and Technology, 2018)
Greywater is one of the point source pollution that negatively impact water resources if not properly treated. However, improvement of greywater quality can be potentially used for irrigation purpose. The main objective of this study is to calculate the lifetime for calcined waste mussel shell (CWMS) in hydrodynamic column. This study was performed using laboratory scale hydrodynamic column filled with CWMS to determine the breakthrough curve, adsorption capacity, accumulation rate and lifetime using empirical model for the adsorption of PO4-3 onto CWMS from greywater. The bed height and flow rate that used in the experiment are 200 mm and 80 mL/h, respectively. The results demonstrate that breakthrough and exhaustion times are 12h and 18h, respectively. The empirical model was verified using experimental equilibrium data. The values of k1 and qmax calculated using model equations are 0.122 mg/g h2 and 0.0017 mg/g, respectively. On the basis of the results, CWMS can be economically basis media used as an adsorbent for the removal of PO4-3 from greywater in the hydrodynamic column.
Keywords: Adsorption; Calcined waste mussel shell; Empirical model; Greywater